Desain Pembelajaran PMRI Materi Penjumlahan Bilangan dengan Menggunakan Media Pohon Pintar di Kelas I Madrasah Ibtidaiyah Al-Amin Cabalu Kecamatan Tanete Riattang Barat Kabupaten Bone - Irma, Irma; Basri, Hasan (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The main problems in this study are 1) How is the PMRI design learning design using smart tree media in the number addition material in class I MI AL-Amin Cabalu, Tanete Riattang Barat District, Bone Regency? 2) How is the Learning Trajectory (learning trajectory) using smart tree media in helping students of Madrasah Ibtidaiyah Al-Amin Cabalu in understanding the concept of addition? This research is a design research research which consists of three stages, namely preliminary design, teaching experiment and retrospective analysis. Research conducted directly in the field to obtain the necessary data and research whose object is about the learning process of a community group. The techniques used include: observation, interviews and documentation. The results of this study indicate that learning mathematics using the PMRI learning design uses smart tree media. Where learning is designed with Learning Trajectory (learning trajectory) which consists of three activities, namely Activity 1. Organizing objects/objects using familiar numbers, Activity 2. Knowing the concept of storing in the process of adding two numbers, and Activity 3. Performing addition operations through games smart tree card. Based on the Learning Trajectory (learning trajectory) the activities developed were able to foster a sense of enthusiasm for students in learning, especially learning mathematics and were able to help MI Al-Amin Cabalu students in understanding the concept of addition.